2014
DOI: 10.3386/w19977
|View full text |Cite
|
Sign up to set email alerts
|

How Do Electricity Shortages Affect Industry? Evidence from India

Abstract: We estimate the effects of electricity shortages on Indian manufacturers, instrumenting with supply shifts from hydroelectric power availability. We estimate that India's average reported level of shortages reduces the average plant's revenues and producer surplus by five to ten percent, but average productivity losses are significantly smaller because most inputs can be stored during outages. Shortages distort the plant size distribution, as there are significant economies of scale in generator costs and shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Conversely, other studies have shown that intermittent, unreliable electricity, and unexpected outages or surges can hurt firm performance. Power outages cost businesses in terms of lost sales (e.g., Allcott, Collard-Wexler, and O'Connell, 2015;Beenstock, Goldin, and Haitovsky, 1997;Adenikinju, 2005) as well as equipment damage, as documented by Foster and Steinbuks (2009). Alam (2013) provided evidence of heterogeneity in the effect of outages, showing that power outages lower profits and output of some electricity-intensive industries in India, but not across the board.…”
Section: Manuel Barronmentioning
confidence: 99%
“…Conversely, other studies have shown that intermittent, unreliable electricity, and unexpected outages or surges can hurt firm performance. Power outages cost businesses in terms of lost sales (e.g., Allcott, Collard-Wexler, and O'Connell, 2015;Beenstock, Goldin, and Haitovsky, 1997;Adenikinju, 2005) as well as equipment damage, as documented by Foster and Steinbuks (2009). Alam (2013) provided evidence of heterogeneity in the effect of outages, showing that power outages lower profits and output of some electricity-intensive industries in India, but not across the board.…”
Section: Manuel Barronmentioning
confidence: 99%
“…Electricity access expansion has found to positively impact industrial growth through increases in production levels and in the number of industrial activities (Rud 2012;Peters et al 2011). Quality of electric supply has also been shown to have important impacts on revenues, productivity, investments (Allcott et al 2016;Fisher-Vanden et al 2012;Reinikka and Svensson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…An unreliable power supply can cause disruptions in the production process that have adverse effects on firm performance and profitability (Fosu, Mlambo, and Oshikoya 2001). In a study of Indian textile firms, Allcott, Collard-Wexler, and O'Connell (2014) found that power outages reduce output by 5 percent. Firms without a generator and small firms experienced higher losses.…”
Section: Firm-level Evidencementioning
confidence: 99%
“…However, using a generator leads to an increase in electricity cost, which enters the profit function as an output tax. Allcott, Collard-Wexler, and O'Connell (2014) note that even if it has a generator, a firm's productivity will be lower due to an input variation effect. On the other hand, firms without a generator experience a shutdown effect, which not only reduces output but also their demand for non-storable inputs.…”
Section: Firm-level Evidencementioning
confidence: 99%